Answer:
78°
Step-by-step explanation:
Since, angles A and B are complementary.
[tex]\therefore m\angle A + m\angle B = 90\degree \\
\therefore (3x+9)\degree + (x - 11)\degree = 90\degree \\
\therefore (3x +x +9-11)\degree = 90\degree \\
\therefore (4x - 2)\degree = 90\degree \\
\therefore 4x - 2 = 90\\
4x = 90+2\\
4x = 92\\ \\ x = \frac{92}{4} \\ \\ x = 23 \\ \\ \because m\angle A = (3x+9)\degree \\ \therefore \: m\angle A = (3 \times 23+9)\degree \\ \therefore \: m\angle A = (69+9)\degree \\ \huge \red{ \boxed{ \therefore \: m\angle A = 78\degree }}[/tex]